Large extracellular vesicles transfer more prions and infect cell culture better than small extracellular vesicles - Soukup, Jakub; Moško, Tibor; Kereïche, Sami; Holada, Karel (Biochemical and biophysical research communications, 2023)
Prions are responsible for a number of lethal neurodegenerative and transmissible diseases in humans and animals. Extracellular vesicles, especially small exosomes, have been extensively studied in connection with various diseases. In contrast, larger microvesicles are often overlooked. In this work, we compared the ability of large extracellular vesicles (lEVs) and small extracellular vesicles (sEVs) to spread prions in cell culture. We utilized CAD5 cell culture model of prion infection and isolated lEVs by 20,000×g force and sEVs by 110,000×g force. The lEV fraction was enriched in β-1 integrin with a vesicle size starting at 100 nm. The fraction of sEVs was partially depleted of β-1 integrin with a mean size of 79 nm. Both fractions were enriched in prion protein, but the lEVs contained a higher prion-converting activity. In addition, lEV infection led to stronger prion signals in both cell cultures, as detected by cell and western blotting. These results were verified on N2a-PK1 cell culture. Our data suggest the importance of lEVs in the trafficking and spread of prions over extensively studied small EVs.
Keywords: Exosomes; Extracellular Vesicles; priony; Animals; lidé; buněčné kultury; extracelulární vezikuly; integriny; exozómy; zvířata; Cell Culture Techniques; Integrins; Prions; Humans